Chronic Heart Failure in Patients with Arterial Hypertension Associated with Obstructive Sleep Apnea Syndrome: Possible Options to Pathogenetic Therapy - A. V. Yakovlev; S. N. Shilov; E. N. Berezikova; N. F. Yakovleva; A. T. Teplyakov; E. V. Grakova; K. V. Kopeva; I. A. Efremov (Рациональная фармакотерапия в кардиологии, 2021)
Aim. To study approaches to the treatment of chronic heart failure (CHF) with reduced and mid-range left ventricular ejection fraction (LVEF) in patients with arterial hypertension (AH) against the background of obstructive sleep apnea (OSA).Material and methods. The study included 136 patients with CHF and AH. Inclusion criteria for the study: 1) moderate and severe OSA (with an apnea/hypopnea index of more than 15 per hour); 2) II-IV functional class of CHF according to NYHA; 3) the level of brain natriuretic peptide precursor (NT-proBNP) ≥125 pg/ml; 3) LVEF <50%; 4) the duration of hypertension is at least 2 years. Patients received drug therapy, including beta-blockers, mineralocorticoid receptor antagonists, diuretics, ACE inhibitors or angiotensin receptor inhibitors or valsartan/sacubitrile. After 12 months of followup, the patients were divided into 2 groups depending on the medication being administered. Group 1 included patients (n = 50) receiving therapy with valsartan/sacubitril, group 2 included patients (n = 86) receiving therapy without this drug. Effective CPAP-therapy also was registered in each group.Results. In patients with CHF who received valsartan/sacubitril, disease progression was recorded in 28% of cases, while in patients who did not receive therapy with this drug, an unfavorable course of CHF was recorded in 42.8% (p = 0.001). In group 1, the NT-proBNP level significantly (p = 0.034) decreased by 34%, while in group 2, a significant (p = 0.002) increase in biomarker levels was revealed by 35.5%. In the group of patients receiving therapy with valsartan/sacubitril an increase in LVEF (p = 0.007) was revealed by 12.5%. In group 1, an increase in exercise tolerance was achieved in the form of a significant (p = 0.012) increase in the distance of the six-minute walk test by 18.2%, while in group 2, the six-minute walk distance decreased by 19.2% (p = 0.034). In the subgroup of patients receiving CPAP therapy in combination with valsartan/sacubitril therapy (n=8), LVEF increased by 11.6% (p = 0.043), the six-minute walk test distance increased by 29.7% (p = 0.046), and NT-proBNP decreased by 22.5% (p = 0.039), while in the group of patients who received only CPAP therapy (n=19).Conclusion. The most significant slowdown in the rate of progression of CHF in patients with AH associated with OSA, an increase in exercise tolerance, as well as the most pronounced tendency to the reverse development of pathological echocardiographic changes in the myocardium when using valsartan/sacubitrile in drug therapy in combination with effective hardware CPAP therapy.